Disruption of the Serotonergic System after Neonatal Hypoxia-Ischemia in a Rodent Model. (8th February 2012) - Buller, Kathryn M.; Wixey, Julie A.; Reinebrant, Hanna E.
Abstract : Identifying which specific neuronal phenotypes are vulnerable to neonatal hypoxia-ischemia, where in the brain they are damaged, and the mechanisms that produce neuronal losses are critical to determine the anatomical substrates responsible for neurological impairments in hypoxic-ischemic brain-injured neonates. Here we describe our current work investigating how the serotonergic network in the brain is disrupted in a rodent model of preterm hypoxia-ischemia. One week after postnatal day 3 hypoxia-ischemia, losses of serotonergic raphé neurons, reductions in serotonin levels in the brain, and reduced serotonin transporter expression are evident. These changes can be prevented using two anti-inflammatory interventions; the postinsult administration of minocycline or ibuprofen. However, each drug has its own limitations and benefits for use in neonates to stem damage to the serotonergic network after hypoxia-ischemia. By understanding the fundamental mechanisms underpinning hypoxia-ischemia-induced serotonergic damage we will hopefully move closer to developing a successful clinical intervention to treat neonatal brain injury.